2008
DOI: 10.1073/pnas.0711613105
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 regulates human mammary stem/progenitor cell fate

Abstract: Although it is well established that women with germ-line mutations in the BRCA1 gene have a greatly increased lifetime incidence of breast and ovarian cancer, the molecular mechanisms responsible for this tissue-specific carcinogenesis remain undefined. The majority of these breast cancers are of the basal-like phenotype characterized by lack of expression of ER, PR, and ERBB2. Because this phenotype has been proposed to resemble that of normal breast stem cells, we examined the role of BRCA1 in human mammary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
370
3
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 406 publications
(410 citation statements)
references
References 32 publications
33
370
3
4
Order By: Relevance
“…These observations support the finding that Brca1-deficient ER-negative primary mammary progenitor cells are defective in their ability to differentiate into ER-positive luminal cells in vitro (Liu et al, 2008) and that aberrant luminal progenitor cells are expanded in breast tissue from human BRCA1 mutation carriers (Lim et al, 2009) …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These observations support the finding that Brca1-deficient ER-negative primary mammary progenitor cells are defective in their ability to differentiate into ER-positive luminal cells in vitro (Liu et al, 2008) and that aberrant luminal progenitor cells are expanded in breast tissue from human BRCA1 mutation carriers (Lim et al, 2009) …”
Section: Discussionsupporting
confidence: 76%
“…Tumours arising in BRCA1 mutation carriers and Brca1 conditional knockout mice have a distinct histopathological and molecular phenotype, including high grade, high mitotic index and expression of basal and stem cell-associated genes (Lakhani et al, 1998;Sorlie et al, 2003;Liu et al, 2008;Shakya et al, 2008;Wright et al, 2008a, b). It has been suggested that BRCA1-associated tumours arise in the basal or stem cell compartments of the mammary gland (Foulkes et al, 2003), although there is also evidence to suggest that that these characteristics may arise as a consequence of BRCA1 loss in other mammary cell types (Liu et al, 2008;Smart et al, 2008). Although the detailed pathway between BRCA1 disruption and breast tumour development has yet to be fully elucidated, recent findings suggest that tumours arising in human BRCA1 mutation carriers may arise from mammary luminal progenitor cells of the mammary gland (Lim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Of the canonical pathways from Ingenuity Pathway Analysis represented by our own TIC gene signature, Notch was one of the top upregulated pathways. Recent evidence also suggest that both hereditary breast cancers in BRCA1 carriers [46], as well as sporadic breast cancers driven by HER2 amplification, may result from dysregulation of stem cell self-renewal pathways. Our preliminary data from a neoadjuvant lapatinib study suggests that breast cancer stem cells are relatively resistant the chemotherapy, but are affected by the EGFR/HER2 inhibitor lapatinib [5].…”
Section: Targeting Tics In Human Breast Cancersmentioning
confidence: 99%
“…The hormonal environment associated with these stages might affect breast cancer risk by increasing or reducing the total number of replicating stem cells, their lineagespecific differentiation to myoepithelial and luminal cells, and eventually the number of cells at risk for malignant transformation (Trichopoulos et al, 2005). There is accumulating evidence for the hypothesis that breast cancer risk is determined in part by the number of susceptible breast stem/progenitor cells that can serve as targets for transformation (Liu et al, 2008).…”
Section: Stem Cellsmentioning
confidence: 99%